Review of factors that influence leadership styles among top management in small and medium size enterprises - Othman, Jamilah; Alby, Jeffrey Lawrence D'Silva; Mohammed, Kabeer Abdullahi (Medwell Journals, 2012)
Leadership styles among top management in small and medium size enterprises are important in the development of these enterprises. The focus of this study is to identify the enabling factors that will influence the leadership styles in small and medium size enterprises. Data for this study was obtained from previous literature. It was identified that four dimensions of transformational leadership and three dimensions of transactional leadership and in addition some socio-demographic factors have the potential to influence leadership styles.